Conceptual Metaphors in Reporting on the COVID-19 Pandemic in Japan’s NHK Newspaper: A Cognitive Semantics Analysis - Mustaqim, Ilham Hijrah; Nur, Tajudin (Universitas Pendidikan Indonesia (Indonesia University of Education), 2022)
This research is a cognitive semantic study using qualitative methods on conceptual metaphors used in reporting on the COVID-19 pandemic in Japan. The theory used is conceptual metaphor theory by Lakoff and Johnson (2003) and image schema theory by Croft and Cruse (2004). The data collection method used was the method of free-living and proficient viewing, while the data review method used was the referential equivalent method. The data was taken from six online news articles in the Japanese-language NHK newspaper. This study aims to describe the classification of conceptual metaphors and image schemes that appear in the news regarding the handling of the COVID-19 pandemic in Japan. There were 13 data found, which were divided into 3 structural metaphors, 4 orientational metaphors, and 6 ontological metaphors. Based on the image schema, the data is also divided into 5 forces, 4 scales, 1 space, 1 existence, and one schemes container. The concept mapping of the metaphor in this study is the depiction of COVID-19 as an enemy, government policies as medicine, and the process of handling COVID-19 as a way forward on the road. In terms of image schema, the metaphor used tends to be a force, depicting COVID-19 as an opponent or obstacle.